Participation of dectin-1 receptor on NETs release against Paracoccidioides brasiliensis: role on extracellular killing - Bachiega, Tatiana Fernanda [UNESP]; Dias-Melicio, Luciane Alarcão [UNESP]; Fernandes, Reginaldo Keller [UNESP]; Balderramas, Helanderson de Almeida [UNESP]; Rodrigues, Daniela Ramos [UNESP]; Ximenes, Valdecir Farias [UNESP]; Soares, Ângela Maria Victoriano de Campos [UNESP] (Elsevier B. V., 2015)
Paracoccidioides brasiliensis is a dimorphic fungus from the Paracoccidioides genus, which is the causative agent of paracoccidioidomycosis, a chronic, subacute or acute mycosis, with visceral and cutaneous involvement. This disease that is acquired through inhalation primarily attacks the lungs but, can spread to other organs. Phagocytic cells as neutrophils play an important role during innate immune response against this fungus, but studies on antifungal activities of these cells are scarce. In addition to their ability to eliminate pathogens by phagocytosis and antimicrobial secretions, neutrophils can trap and kill microorganisms by release of extracellular structures composed by DNA and antimicrobial proteins, called neutrophil extracellular traps (NETs). Here, we provide evidence that P. brasiliensis virulent strain (P. brasiliensis 18) induces NETs release. These structures were well evidenced by scanning electron microscopy, and specific NETs compounds such as histone, elastase and DNA were shown by confocal microscopy. In addition, we have shown that dectin-1 receptor is the main PRR to which fungus binds to induce NETS release. Fungi were ensnared by NETs, denoting the role of these structures in confining the fungus, avoiding dissemination. NETs were also shown to be involved in fungus killing, since fungicidal activity detected before and mainly after neutrophils activation with TNF-α, IFN-γ and GM-CSF was significantly inhibited by cocultures treatment with DNAse.
Keywords: Dectin-1 receptor; Innate immunity; Neutrophil; Neutrophil extracellular traps; Paracoccidioides brasiliensis